2013
DOI: 10.1017/dmp.2013.40
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness of Anesthesiologists Working in Humanitarian Disasters

Abstract: As the lack of preparation and relevant training can create precarious situations, anesthesiologists and deploying agencies should improve preparedness for anesthesia personnel. (Disaster Med Public Health Preparedness. 2013;0;1-5).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Anesthesiologists working in disaster and humanitarian settings are required to perform high-quality anesthesia in challenging conditions and must be prepared to perform unfamiliar tasks 22 with limited access to resources. Unfortunately, a recent study has demonstrated that anesthesiologists deployed in complex emergencies still lack important preparedness before deployment 22 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anesthesiologists working in disaster and humanitarian settings are required to perform high-quality anesthesia in challenging conditions and must be prepared to perform unfamiliar tasks 22 with limited access to resources. Unfortunately, a recent study has demonstrated that anesthesiologists deployed in complex emergencies still lack important preparedness before deployment 22 …”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] A plausible explanation for these results might be self-funding requirements, lack of organization, and time constraints. [19][20][21][22][23][24][25][26] Most of the respondents, particularly those with prior experience, believe that participation in humanitarian missions can contribute to professional development. Accordingly, Drain et al 27 published a detailed description of the role that humanitarian aid rotations play in the professional development of medical students through strengthening clinical, decisionmaking skills, and problem-solving skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Educational needs were established on the basis of an expert opinion survey [ 9 ], round tables with CRIMEDIM and MSF field experts, and a literature review of published competency sets for humanitarian workers [ 10 ]. Since our training program targeted health workers but was meant to be extendable in the future to other sectors operating under the umbrella of humanitarian aid, four manuscripts were selected on the basis of their cross-sectorial approach [ 6 ] and definition of discipline-specific competencies relevant to our audience [ 11 13 ]. These competency sets served as a foundational basis for the course curriculum and were translated into 10 cross-sectorial and 1 profession-specific competency domain for each specialty [Table 1 ].…”
Section: Methodsmentioning
confidence: 99%
“…Educational needs were established on the basis of an expert opinion survey (9),round tables with CRIMEDIM and MSF eld experts, and a literature review of published competency sets for humanitarian workers (10).Since our training program targeted health workers but was meant to be extendable in the future to other sectors operating under the umbrella of humanitarian aid, four papers were selected on the basis of their cross-sectorial approach(6) and de nition of discipline-speci c competencies relevant to our audience (11)(12)(13).These competency sets served as a foundational basis for the course curriculum and were translated into 10 cross-sectorial and 1 profession-speci c competency domain for each specialty [ Table 1]. Learning objectives were phrased according to Bloom's Taxonomy.…”
Section: Curriculummentioning
confidence: 99%